2013
DOI: 10.1177/1350650113481147
|View full text |Cite
|
Sign up to set email alerts
|

Application of the fluid–structure interaction technique for the analysis of hydrodynamic lubrication problems

Abstract: Fluid-structure interaction technique seems to be one of the most promising possibilities for theoretical analysis of lubrication problems. It allows coupling of different physical fields in one computational task, taking into account the interaction between them. In this article, two sets of fluid-structure interaction analyses focusing on the bearing performance evaluation are presented. One analysis was applied to a water-lubricated journal bearing and the other to a hydrodynamic thrust bearing lubricated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The traditional method for hydrodynamic journal bearing analysis usually applies the lubrication theory based on classical Reynolds equation (Brizmer et al [1], Buscaglia et al [2], D'Agostino and Senatore [3]) which is simplified form of Navier-Stokes equations (Arghir et al [4], Sahlin et al [5], Li et al [6]. and Wodtke et al [7]) and continuity equation with usual thin film assumptions and thus has limitations in its applications. The solution of Reynolds equation is obtained using finite difference or finite element methods which lead to the subsequent development of simulation codes that integrate various numerical and empirical models taking into account physical phenomena such as turbulence, heat transfer, and cavitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional method for hydrodynamic journal bearing analysis usually applies the lubrication theory based on classical Reynolds equation (Brizmer et al [1], Buscaglia et al [2], D'Agostino and Senatore [3]) which is simplified form of Navier-Stokes equations (Arghir et al [4], Sahlin et al [5], Li et al [6]. and Wodtke et al [7]) and continuity equation with usual thin film assumptions and thus has limitations in its applications. The solution of Reynolds equation is obtained using finite difference or finite element methods which lead to the subsequent development of simulation codes that integrate various numerical and empirical models taking into account physical phenomena such as turbulence, heat transfer, and cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…This result differs from the Reynolds boundary condition solution to determine the onset of cavitation resulting in an increased pressure build-up. Wodtke et al [7] and Lin et al [8] worked on the analysis of bearings with cavitation coupled with FSI and found that the deformations are significant. Also, the cavitation problem becomes more severe with an increase in speed and significant computation time is required as observed by Geller et al [20], Riedel et al [21], Osman [22] and Montazeri [23].…”
Section: Introductionmentioning
confidence: 99%
“…The rotation speed was found to play a dominant role in augmenting the lubricant temperature and promoting the cavitation formation, which implies serious constrains on the design of highly-rotating journals. The isothermal operation of journal bearings was investigated numerically by (Wodtke, Olszewski and Wasilczuk, 2013), where the formation of cavitation was predicted in terms of the operating conditions examined. Unlike the case of water-lubricated journal bearings, it was observed that the negative lubricant pressure has no obvious impact on the performance of oil-lubricated bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Wodtke et al. 34 considered steady-state operation in two cases using fluid–structure interaction (FSI), in which one analysis was applied to a water-lubricated journal bearing and the other to a hydrodynamic thrust bearing lubricated with oil. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%